Development of expression markers for reduced susceptibility in Fraxinus excelsior - Stein Åslund, Matilda (SLU/Dept. of Forest Mycology and Plant Pathology, 2018)
Common ash (Fraxinus excelsior) extends throughout temperate Europe, and in southern and central Sweden it is one of the most common broad-leaved deciduous trees. It is economically valuable thanks to its elastic, hard and pressure-resistant wood, and pollarded ash trees provide a cultural heritage in many European landscapes. The species is also important for biodiversity, as many organisms depend on it. F. excelsior is currently suffering from ash dieback disease, an epidemic caused by the fungus Hymenoscyphus fraxineus. Ash dieback lethally affects trees of all ages. Common ash is listed as ‘endangered’ in the Red list of Sweden since 2015, due to trees being affected by dieback all over the F. excelsior distribution range in the country.